Teacher training policies in the pedagogy course: challenges and perspectives of graduates from a Community Higher Education Institution (2019-2022) - Trevisol, Marcio (2025)
The article is the result of a CNPq productivity survey, which has as one of its research sites the Pedagogy course at the University of the West of Santa Catarina (Unoesc). The objective of this project section was to map the graduates of the pedagogy course at the Community Higher Education Institution, in order to assess the working conditions, socioeconomic status and satisfaction of these pedagogues with their (initial) training. This is a qualitative and exploratory research, with subjects who graduated from the Capinzal and Campos Novos campi from 2019 to 2022. Data were collected through a semi-structured questionnaire organized using the Likert Scale. The research showed that graduates of the pedagogy course face different challenges in exercising the profession, such as the lack of opportunities, financial devaluation and temporary work hiring. Therefore, it is recommended the implementation of educational policies aimed at hiring teachers recently graduated through public examinations, with employment incentives so that they can continue their studies. The research demonstrated that it is necessary to create policies to encourage the insertion of pedagogues into the world of research, in addition to increasing the salary of these professionals.